Impact assessment and quality analysis of corporate social responsability (CSR) programs of mining companies and their contribution to sustainable development in the communities they operate: case study Tenke Fungurume Mining SA in the Democratic Republic of Congo (DRC) - Kabila, Jaynet Desire (2015)
Purpose – This case study presents an impact assessment of Corporate Social Responsibility (CSR) programs of the TFM Company in order to understand how they contribute to the sustainable development of communities in areas in which they operate. Design/Methodology/Approach - Data for this study was collected using qualitative data methods that included semi-structured interviews and Focus Group Discussions most of them audio and video recorded. Documentary analysis and a field visit were also undertaken for the purpose of quality analysis of the CSR programs on the terrain. Data collected was analyzed using the Seven Questions to sustainability (7Qs) framework, an evaluation tool developed by the Mining, Minerals and Sustainable Development (MMSD) North America chapter. Content analysis method was on the other hand used to examine the interviews and FGDs of the study participants. Findings - Results shows that CSR programs of TFM SA do contribute to community development, as there have been notable changes in the communities’ living conditions. But whether they have contributed to sustainable development is not yet the case as programs that enhance the capacity of communities and other stakeholders to support these projects development beyond the implementation stage and the mines operation lifetime need to be considered and implemented. Originality/Value – In DRC, there is paucity of information of research studies that focus on impact assessment of CSR programs in general and specifically those of mining companies and their contribution to sustainable development of local communities. Many of the available studies cover issues of minerals and conflict or conflict minerals as mostly referred to. This study addressees this gap.